Advanced practice nursing in primary care in OECD countries Recent developments and persisting implementation challenges - Brownwood, Ian (OECD Health Working Papers, 2024)
The pandemic has stimulated growing interest in using advanced practice nurses such as Nurse Practitioners (NPs) to address growing primary care needs linked to population ageing and more people living with chronic conditions, although not all countries are moving at the same speed. This OECD Health Working paper reviews recent developments in advance practice nursing (APN) in primary care in OECD countries. It focusses on NPs in those countries that are recognising this category of nurses, but also describes the emergence of other categories of nurses taking on new roles such as family and community nurses in some European countries. In those countries that have achieved decisive breakthroughs in new forms of task sharing between primary care doctors (GPs) and nurses, increasing the number of APNs in primary care is seen as a real opportunity to respond to primary care needs and reduce pressures on GPs and hospitals